Study On Herzberg Intrinsic Factors Of Motivation - Sobia Saeed, Hina Mushtaq, Sumaira Kanwal M. Musarrat Nawaz (International Journal of Scientific Research and Management (IJSRM), 2015)
This study investigates the intrinsic factors of motivation that are essential and important for employees in educational sector. These factors consist of recognition, achievement motivation, work itself, responsibility, promotion and growth. Highly motivated employees make a huge contribution in long term survival of the organization. This study is based upon the Herzberg intrinsic factors of motivation i.e. motivators. Descriptive research is used in this study. Population of this study consists of the teachers of Public and Private sector universities in Lahore. Multistage sampling technique is used for drawing sample from population. Questionnaire is used as a data collection instrument. 425 Questionnaires were distributed among teachers in different departments of PU, GCU, UVAS and UOL out of which 303 were returned. Descriptive statistics i.e. frequency and percentage is used for data analysis. The findings suggested that employees are highly motivated with all intrinsic factors i.e. achievement, recognition, advancement/growth but less motivated with the promotion policies of the organizations. Organizations should properly formulate the promotion policies to make the employees motivated and productive for the organization. Key Words: Intrinsic, Motivation, Achievement, Recognition, Promotion, Work itself, Growth